HDAC inhibitor-based therapies and haematological malignancy. - Stimson, L; Wood, V; Khan, O; Fotheringham, S; La Thangue, N (2009)
Reversible acetylation mediated by histone deacetylase (HDAC) influences a broad repertoire of physiological processes, many of which are aberrantly controlled in tumour cells. Since HDAC inhibition prompts tumour cells to enter apoptosis, small-molecule HDAC inhibitors have been developed as a new class of mechanism-based anticancer agent, many of which have entered clinical trials. While the clinical picture is evolving and the precise utility of HDAC inhibitors remains to be determined, it is noteworthy that certain tumour types undergo a favourable response, in particular haematological malignancies. Vorinostat (suberoylanilide hydroxamic acid) has been approved for treating cutaneous T-cell lymphoma in patients with progressive, persistent or recurrent disease. Here, we discuss developments in our understanding of molecular events that underlie the anticancer effects of HDAC inhibitors and relate this information to the emerging clinical picture for the application of HDAC inhibitors in haematological malignancies.